2000
DOI: 10.1016/s0301-4622(00)00199-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative calorimetric study of non-amyloidogenic and amyloidogenic variants of the homotetrameric protein transthyretin

Abstract: Ž. Familial amyloidotic polyneuropathy FAP is an autosomal dominant hereditary type of amyloidosis involving Ž . amino acid substitutions in transthyretin TTR . V30M-TTR is the most frequent variant, and L55P-TTR is the variant associated with the most aggressive form of FAP. The thermal stability of the wild-type, V30M-TTR, L55P-TTR and a non-amyloidogenic variant, T119M-TTR, was studied by high-sensitivity differential scanning Ž . calorimetry DSC . The thermal unfolding of TTR is a spontaneous reversible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
6
38
0
Order By: Relevance
“…Such an effect is reminiscent of that observed for I84S and I84A TTR variants, for which a large conformational change in the region hosting the mutation was induced by the lowering of the pH (32). Although limited, at least at neutral pH, the above described structural perturbations induced in TTR by amyloidogenic mutations possibly represent early events correlated with a destabilization of the TTR structure, in accordance with several lines of evidence indicating that amyloidogenic TTR variants are more prone to denaturation and amyloid aggregation relative to wild-type TTR (22,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Crystal Structures Of Amyloidogenic Ttr Variants At Neutralsupporting
confidence: 84%
“…Such an effect is reminiscent of that observed for I84S and I84A TTR variants, for which a large conformational change in the region hosting the mutation was induced by the lowering of the pH (32). Although limited, at least at neutral pH, the above described structural perturbations induced in TTR by amyloidogenic mutations possibly represent early events correlated with a destabilization of the TTR structure, in accordance with several lines of evidence indicating that amyloidogenic TTR variants are more prone to denaturation and amyloid aggregation relative to wild-type TTR (22,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Crystal Structures Of Amyloidogenic Ttr Variants At Neutralsupporting
confidence: 84%
“…More recently, micro-calorimetric work [44] and pressure-induced unfolding experiments followed by NMR [45] confirmed in a more quantitative way this earlier view. In fact, the micro-calorimetric studies showed that, at pH 7.0 and relatively high protein concentrations (6.2 µM tetramer) both amyloidogenic and nonamyloidogenic variants of TTR showed very high transition temperatures (T m ) for thermal unfolding.…”
Section: Stability and Conformational Fluctuations Of Tetrameric Ttrsupporting
confidence: 52%
“…Additionally, the observed small differences in conformational stability do not agree with the relative amyloidogenic potential of the TTR variants studied (21). Thus, differences in the conformational stability of tetrameric TTR do not seem to justify the amyloidogenic character of some TTR variants.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, we showed by differential scanning calorimetry (DSC) of WT-, V30M-, L55P-, and T119M-TTR that the tetrameric forms of these variants are highly stable to thermal unfolding (21). Additionally, the observed small differences in conformational stability do not agree with the relative amyloidogenic potential of the TTR variants studied (21).…”
Section: Discussionmentioning
confidence: 98%